Electronic collection system SER - Electronic Government in Colombia (2018)
This essay talks about the need we have to experience the technology, how after use we welcome us to it and we enter the comforts that offers; This is how we explain where was born the idea of creating a system of safe effective, agile, modern and affordable to all stakeholders; The electronic collection system is an effective tool in the financial area of the Ministry of information technologies and communications Since it allows to accelerate the process of collection operations reported on line which provides operators system confidence and agility in the fulfillment of obligations, AS has shown to be in constant change oriented to improve its service by correcting faults that arise in the course of its operation which is why every day it is more efficient and competitive to exceeding expectations and goals for their measurement.